Student Wellbeing Differences Reviewed From Learners' Perceptions of Servant Leadership Teachers In State Elementary Schools - Raden Bambang Sumarsono; Sunarni Sunarni; Desi Eri Kusumaningrum; Djum Djum Noor Benty; Athalla Nauval Bhayangkara; Nurul Mustabsyiroh; Sasi Maulina (Graduate School of Universitas Negeri Malang, 2023)
This study aims to determine differences in the level of student wellbeing in terms of student perceptions of teacher performance in applying servant leadership in the learning process. This study uses a correlational quantitative method. The population is 30,980 students. The sample technique used was purposive sampling, with a total of 151 students. Data was collected using a questionnaire technique. Data analysis techniques used descriptive and One-way between groups (ANOVA). The results showed that the level of student welfare was in the very good category, the level of implementation of servant leadership by teachers was in the very good category, and there were differences in student welfare seen from the teacher's perception of the implementation of servant leadership in